2015
DOI: 10.1007/s10278-015-9847-8
|View full text |Cite
|
Sign up to set email alerts
|

Methods on Skull Stripping of MRI Head Scan Images—a Review

Abstract: The high resolution magnetic resonance (MR) brain images contain some non-brain tissues such as skin, fat, muscle, neck, and eye balls compared to the functional images namely positron emission tomography (PET), single photon emission computed tomography (SPECT), and functional magnetic resonance imaging (fMRI) which usually contain relatively less non-brain tissues. The presence of these non-brain tissues is considered as a major obstacle for automatic brain image segmentation and analysis techniques. Therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
117
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 195 publications
(144 citation statements)
references
References 94 publications
1
117
0
1
Order By: Relevance
“…[31][32][33][34][35][36][37][38][39][40][41][42][43] A review on MRI segmentation and brain extraction can be found in. 44,45 Each of these methods has their merits, drawbacks, and limitations. No single method is found to be robust for all types and orientations.…”
Section: Introductionmentioning
confidence: 99%
“…[31][32][33][34][35][36][37][38][39][40][41][42][43] A review on MRI segmentation and brain extraction can be found in. 44,45 Each of these methods has their merits, drawbacks, and limitations. No single method is found to be robust for all types and orientations.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the availability of automatic brain tissue segmentation [9][10][11] in most of the modern software programs for perfusion data analysis, the user-defined thresholding method is still the state-of-the-art technique that is widely used as a way of managing pixels involved in brain perfusion ROI.…”
Section: Methods Of Researchmentioning
confidence: 99%
“…from an MR image of the whole head, since they are obstacles for automatic analysis [95]. Those non-brain tissues may decrease the detection performance of brain diseases.…”
Section: Image Preprocessingmentioning
confidence: 99%